2018
DOI: 10.18632/oncotarget.24889
|View full text |Cite
|
Sign up to set email alerts
|

The versatile nature of miR-9/9* in human cancer

Abstract: miR-9 and miR-9* (miR-9/9*) were first shown to be expressed in the nervous system and to function as versatile regulators of neurogenesis. The variable expression levels of miR-9/9* in human cancer prompted researchers to investigate whether these small RNAs may also have an important role in the deregulation of physiological and biochemical networks in human disease. In this review, we present a comprehensive overview of the involvement of miR-9/9* in various human malignancies focusing on their opposing rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 100 publications
3
50
0
Order By: Relevance
“…Recent studies showed that CDX2 targets the multidrug resistance gene MDR1 (ABCB1) and CFTR (ABCC7), coding for two ATP-dependent drug efflet pumps [36][37][38]. These genes are significantly down-regulated in CDX2-negative cell lines and CDX2-negative patient tumors and have also been reported to promote the response to chemotherapy [24,38]. This supports our results showing that CDX2-positive cases show a poor response to chemotherapy which may be effective in patients with CDX2-negative CRC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies showed that CDX2 targets the multidrug resistance gene MDR1 (ABCB1) and CFTR (ABCC7), coding for two ATP-dependent drug efflet pumps [36][37][38]. These genes are significantly down-regulated in CDX2-negative cell lines and CDX2-negative patient tumors and have also been reported to promote the response to chemotherapy [24,38]. This supports our results showing that CDX2-positive cases show a poor response to chemotherapy which may be effective in patients with CDX2-negative CRC.…”
Section: Discussionmentioning
confidence: 99%
“…The mature miR-9 transcript is produced by three independent genes: miR-9-1, miR-9-2, and miR-9-3. Of miR-9-5p and miR-9-3p which are mature miR-9s, miR-9-5p is dominant in humans [24] (Figure 4a). We performed cell proliferation, cell cycle, and cytotoxicity assays using DLD-1 cells overexpressing miR-9-1 (DLD-1-miR-9-1) which stably expresses miR-9-5p ( Figure 4b).…”
Section: Overexpression Of Mir-9-1 Accelerates Cell Cycle and Cell Prmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies demonstrate clear similarities between miR-9 expression and function in Drosophila and vertebrates. Disrupted miR-9 function has also been linked with some human pathologies, including cancer progression (Nowek et al 2018) and neurodegenerative amyloid diseases (Packer et al 2008). For instance tumorigenic cells from medulloblastoma appear to have decreased expression of miR-9, while a subclass of glioblastoma tumour cells express miR-9 at a higher level (Ferretti et al 2009;Kim et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…MiR-9 is highly expressed in brain, where it is involved in neural stem cell self-renewal and differentiation (Zhao et al, 2009) , and synaptic plasticity (Sim et al, 2016) . Mir-9 levels are also dysregulated in many human cancers Nowek et al, 2018) . Consistent with a role for Drosha cleavage fidelity in driving function, an isomiR of miR-9 with an altered 5' end was detected in human embryonic stem cells and neural cells and shown to affect target site selection of several reporter constructs (Tan et al, 2014.).…”
Section: Introductionmentioning
confidence: 99%